Olanzapine induced hyperprolactinemia - Nayak, Veena; Devaramane, Virupaksha; Mallya, Deepak; Bhandary, Panambur V. (International Journal of Basic & Clinical Pharmacology, 2017)
Olanzapine, a second generation antipsychotic is widely used for the treatment of schizophrenia and bipolar disorders. Though olanzapine is an efficacious antipsychotic it has been associated with many adverse effects like weight gain, hyperlipidemia, diabetes mellitus, etc necessitating its discontinuation. Here, we present two cases of hyperprolactinemia induced by olanzapine.